EFFECT OF COLCHICINE ON CELLULAR IMMUNE RESPONSES IN MICE - S. Khurram; A. Javeed; M. Ashraf; D. A. Hamdani; J. Nazir; M. S. Yousaf; A. Ghafoor (Journal of Animal and Plant Sciences, 2017)
Colchicine is microtubule inhibiting agent used for thecure of various skin ailments causing inflammation and reduction of pain in gouty arthritis.The current study was designed to evaluate the effect of colchicine on cellular immune responses in mice.Cellular immune responses were assessed indelayed type hypersensitivity (DTH) assay, macrophage engulfment assay, cyclophosphamide induced neutropenic test and nitric oxide (NO) production assay.Colchicine was administered to mice at doses of 40µg/kg, 80µg/kg and 160µg/kg intraperitoneally. Data were statistically analyzed by ANOVA and chi square test. DTH showed significant (P<0.0001) decrease in skin thickness of colchicine treated groups. In macrophage engulfment assay, significant (P<0.0001) decrease in engulfment of sheep red blood cells (SRBCs) was observed by macrophages in colchicine treated groups. Colchicine treated groups showed significant (P<0.0001) reduction of TLC and neutrophil count.NO production difference was significantly (P<0.0001) reduced in macrophages alone and lipopolysaccharide (LPS) stimulated macrophages in colchicine treated groups. Therefore, it is concluded that colchicine suppresses the cellular immune responses in mice.
Keywords: Cellular; Colchicine; Immune; Nitric oxide; Macrophage